Association between inflammatory bowel disease gene 5 (IBD5) and interleukin‐23 receptor (IL23R) genetic polymorphisms in Malaysian patients with Crohn's disease - Chua, Kek Heng; Hilmi, Ida; Lian, Lay Hoong; Patmanathan, Sathya Narayanan; Hoe, See Ziau; Lee, Way Seah; Goh, Khean Lee (Wiley, 2012)
OBJECTIVE: This study was aimed to investigate the possible association of Crohn's disease (CD) with inflammatory bowel disease gene 5 (IBD5) IGR2198a₁ (rs11739135), IGR2096a₁ (rs12521868) and interleukin-23 receptor (IL23R) genetic variant (rs1004819) in the Malaysian population. METHODS: Blood samples from 80 CD patients and 100 healthy controls were recruited. Genomic DNA was extracted and analyzed by polymerase chain reaction-restriction fragment length polymorphism. RESULTS: The results revealed that there was an increased frequency of IGR2198a₁ C allele (8.8 in CD, 1.5 in controls, P < 0.05, OR 6.30, 95 CI 1.7722.31) and IGR2096a₁ T allele (6.9 in CD, 1.5 in controls, P < 0.05, OR 4.85, 95 CI 1.3317.69) in the CD patients as compared to the controls, suggesting the two variants were potential risk factors of CD. Both risk alleles (C and T) were highest in Indians. In contrast, no significant difference was observed for the IL23R gene variant (rs1004819) between these two groups (P = 0.941). All genotypes and alleles of this gene variant were present in equal ratios in the CD and control groups (OR 1.02, 95 CI 0.661.57 for T allele and OR 0.98, 95 CI 0.641.52 for C allele). CONCLUSIONS: There is a strong association between both IBD5 locus variants but not the IL23R gene variant with CD in the Malaysian population. The IBD5 locus variants were highest in Indians, which may explain the increased susceptibility of this particular ethnic group to the disease.